CONCEPTUALIZING COPY/RIGHTS: INTERNET FANDOM, CULTURAL NORMS, AND THE LAW - Stanfill, Mel; Fiesler, Casey; Morrissey, Katherine E.; Noppe, Nele (AoIR Selected Papers of Internet Research, 2015)
The history of media fandom has been one of both early technological adoption and eager intellectual property reuse. Accordingly, fandom is a productive site at which to examine how contemporary culture imagines the Internet, intellectual property law, and creative practice. Conceptualizing Copy/rights approaches these questions using a productively diverse set of analytic frameworks, case studies, and national contexts. As a whole, the panel provides a deeply interdisciplinary look at how beliefs about the law impact the design and use of technology. The Conceptualizing Copy/rights papers identify how people’s beliefs about technology shape their engagement with the law and, in particular, how the practices of fan communities are shaped by their beliefs about technology and intellectual property. The first and second papers conduct in-depth analysis of specific communities and their norms and practices, while the third and fourth provide a complementary focus on how media industries interface with fans in legal and technological ways. In this way, the panel provides a comprehensive look at the conjuncture between fandom, the Internet, and the law. Fandoms are one key contemporary arena where everyday Internet users, individuals without legal training, engage with the complexities of copyright. Moreover, fandoms are sites where media industries enact their interpretations of the law and work to shape digital behavior to facilitate their own interest in profit. Crucially, the legal framework of intellectual property, established in the print era, is increasingly maladapted to the realities of media creation and distribution in the Internet era. This mismatch between the law and production technologies then collides with community ethical norms and media industry goals to produce a variety of intriguing social phenomena. Significantly, community and industry priorities often find themselves at odds with both the law and what is technologically possible. While fandom as a cultural practice long predates networked computing, Internet-based platforms have become vital to fandom in the contemporary era. These technologies are now central to the ways fans and industries negotiate creative practice and the law. All of these papers pose important questions regarding the use of commercialized platforms by current fan communities. In particular, “Selling Unauthorized Digital Remix Works in the U.S. and Japan” and “The Internet Intellectual Property Imaginary” discuss how the intersection of economics and the law plays a key role in the design of technological platforms. These papers outline ways that the affordances selected for inclusion in these platforms can be influenced more by industry beliefs about the law and ethics than they are by the law itself. Another key contribution of these papers is their examination of the ways pre-Internet power structures and cultural practices are adapting to the Internet, much as the law itself is having to be reworked and rethought due to technological change. Thus, Conceptualizing Copy/rights addresses how offline or preexisting socioeconomic inequality impacts access. “Imagined Policies” addresses the longstanding practices of fan communities and the ways their creative practices have adapted to new production technologies and digital networks. “Fandom Problems” (paper 2) identifies the different networks of fans that find themselves united under the label of “fandom” and their often competing norms and interests. Providing a helpful sense of scope or historical change, these papers demonstrate the ways older fan norms and practices are more or less suited to shifting technological and legal realities. Overall, the research presented on this panel examines the ways that fans and media industries make sense of networked technologies and the law, as well as how fans negotiate their relationships with technology, intellectual property, and their communities. Conceptualizing Copy/rights will therefore provide important insight into one key aspect of the contemporary internet imaginary.